Problem (ne)evklidskih okolic pri lepljenju 3-mnogoterosti - Šipec, Katarina (Matrika, 2022)
We descibe gluing polygons along their edges and conclude that we always obtain a surface. Assuming orientability of the surface, this surface is determined. Presented is the problem of Euclidean neighbourhoods of vertices obtained by analogous gluing of octahedron faces in the case that Euclidean neighbourhoods are glued into a cone of a surface of positive genus.
Keywords: Euclidean neighbourhoods; evklidske okolice; gluing 3-manifolds; lepljenje 3-mnogoterosti; matematika; mathematics; ploskve; surfaces